Simulation of a Wheeled Vehicle Dynamic Regimes in Laboratory Conditions - Labuda, Robert; Kovalcik, Andrej; Repka, Jan; Hlavna, Vladimir (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with simulation of wheeled vehicle dynamic regimes in laboratory conditions. Based on the analysis of static and dynamic characteristics of the vehicle and test equipment the calculation model was created that calculates the course of a loading moment on the simulator for the given vehicle and driving regime. The basic condition for the simulation is the requirement for reaching congruent courses of driving speeds at the same vehicle control both on the roadway and in the test room.